Creative Economy Development Toward Stability of National Economy (Indonesia) - Rowandhy Saleh (Journal Research of Social Science, Economics, and Management, 2022)
The creative economy is a new economic force that is based on the country's economy and works as a social and economic measure for disasters. Speed. level in this country. The purpose of this study was to determine the variables related to the country (Indonesia), to find out the level of development affecting the economy, and its effects from 2015-2019. The study of the development of the creative industry in the banking sector that affects the country's economy, uses a qualitative research approach. The results of research with regression show that variables that affect the country's economy have a positive effect on economic growth, while the effectiveness ratio is directly influential, and efficiency directly does not significantly influence the country's economic growth. This can affect the reduction in unemployment rates and the effectiveness.